2014
DOI: 10.1073/pnas.1320486111
|View full text |Cite
|
Sign up to set email alerts
|

Activation induced deaminase C-terminal domain links DNA breaks to end protection and repair during class switch recombination

Abstract: Activation-induced deaminase (AID) triggers antibody class switch recombination (CSR) in B cells by initiating DNA double strand breaks that are repaired by nonhomologous end-joining pathways. A role for AID at the repair step is unclear. We show that specific inactivation of the C-terminal AID domain encoded by exon 5 (E5) allows very efficient deamination of the AID target regions but greatly impacts the efficiency and quality of subsequent DNA repair. Specifically eliminating E5 not only precludes CSR but a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
79
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(86 citation statements)
references
References 53 publications
7
79
0
Order By: Relevance
“…These data are also in agreement with the identification of increased microhomology sequences in switched regions of AID +/-memory B cells, a characteristic associated with less efficient CSR through decreased AID activity (56). Dominant AICDA mutations encoding hyperactive AID variants that cannot catalyze CSR also resulted in decreased SHM frequencies in IgM + memory/marginal zone B cells (57). This paradoxical observation associating hyperactive AID enzyme activity with lower SHM may be reconciled with the possibility that hyperactive AID activity may induce exacerbated DNA lesions in GC B cells, causing B cells that attempt many rounds of antibody gene mutations to undergo apoptosis and be eliminated.…”
Section: Discussionsupporting
confidence: 87%
“…These data are also in agreement with the identification of increased microhomology sequences in switched regions of AID +/-memory B cells, a characteristic associated with less efficient CSR through decreased AID activity (56). Dominant AICDA mutations encoding hyperactive AID variants that cannot catalyze CSR also resulted in decreased SHM frequencies in IgM + memory/marginal zone B cells (57). This paradoxical observation associating hyperactive AID enzyme activity with lower SHM may be reconciled with the possibility that hyperactive AID activity may induce exacerbated DNA lesions in GC B cells, causing B cells that attempt many rounds of antibody gene mutations to undergo apoptosis and be eliminated.…”
Section: Discussionsupporting
confidence: 87%
“…Because the AID C-terminal mutants were all shown to be monomeric, their wide distribution along the gradient suggested that some of the monomers associated with other proteins and RNAs. Collectively, these results showed that AID distributed in the LMW region could be subdivided into a narrow region of exclusive monomer (fractions 3-4) and a broader region of monomer and dimer (fractions [5][6][7][8][9][10][11][12] and that the HMW fractions of AID seemed to contain dimers.…”
Section: Detection Of Apobec Homodimer Formation By the Monomeric Kusmentioning
confidence: 77%
“…In the present study, we demonstrated that specific AID-associated RBPs have the potential to direct AID's function toward either DNA cleavage or recombination. Because CSR recombination can be regulated at either the S-S synapse or the DNA end-processing repair phase (6,11,12), we speculate that at least two independent mRNAs are involved (7,11,60). Thus, it is reasonable to propose that distinct RBPs are involved in AID-RNP complex formation and that their KD affects different stages of CSR.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations